Moral Transvaluation of Nationality of Community Organizations in Indonesia (A Critical Study of Nahdlatul Ulama's National Morals: Pancasila Perspective and the 1945 Constitution) - Najamudin, Najamudin (Jurnal Review Politik, 2024)
The offer of the ideal form of the state continues to be championed by various community organizations in Indonesia, radically and clandestinely. This study explores the moral transvaluation of the Nationality of community organizations through in-depth research of community organizations' interpretations of Pancasila and the 1945 Constitution. The author argues that community organizations have and are carrying out moral transvaluations that utilize state power to realize the ideology of community organizations. This normative legal research uses a statutory approach to answer research questions and uses Pancasila and the 1945 Constitution to assess the moral transvaluation of the Nationality of community organizations. Based on the study's results, the moral transvaluation of community organizations is caused by first-past defeats due to global and national political inferiority. Second, community organizations seize various government positions for the sake of ideologization. The community needs to know the moral transvaluation of the Nationality of community organizations to strengthen the values of unity, justice, and even humanity in the nation, state, and religion.